Effect of Fire-Retardant Ratios in Kenaf Fiber for Fire Resistance Properties and Acoustical Performance - Ayol, Myia Yuzrina Zalkis; Yaakob, Mohd Yuhazri; Tomy, Meryl Anyie; Mohamed, Kamarul Amir; Wan Mahmood, Wan Hasrulnizzam; Abdul Rashid, Azrin Hani; Achmad Jusuf, Zulfikar (International Journal of Integrated Engineering, 2024)
Nowadays, awareness towards environmental issues increases significantly where people have learned the important of protecting environment for a better future. Thus, this study investigated the embedded kenaf fiber as a natural material with different of fire-retardant loading content towards the fire resistance properties and acoustical performance for insulator application in future building component. Based on the study conducted toward the prepared size 200 mm x 2000 mm x 40 mm of fixed kenaf composition with various fire retardant by 5 wt. % and increasing gradually to 25 wt. %, this study found that the highest value of thermal conductivity which is 0.4472 W/mK and temperature different of 240 °C for S1. Also, this study found the higher percentage of non-burn fiber which is 98.103 % for S6 and the highest peak of 0.9104 coefficient at 1259 Hz and at 1600 Hz with coefficient of 0.9091 for S3. This study showed that kenaf fiber embedded with different of fire-retardant loading content have a potential to replace the current insulator used in industry.